ASSET-BASED DAKWAH STRATEGY: REVITALIZING THE FUNCTION OF MOSQUES AS POST-DISASTER RECOVERY CENTERS - Muharram (CV Naskah Aceh, 2026)
This research is motivated by the problematic gap between the empirical reality of post-disaster mosque functions, which tend to be passive and reactive, serving only as public kitchens, logistics warehouses, and temporary refugee camps, and their ideal potential as active and strategic recovery centers. This research aims to formulate an asset-based da'wah strategy to revitalize the function of mosques as post-disaster recovery centers. The type of research used is library research with data sources from books, international and national scientific journal articles, and research reports. Data collection techniques are carried out through identification, searching, analysis, selection, and organization of relevant sources. Data validity testing is carried out through source triangulation, peer debriefing, thick descriptions, audit trails, and confirmability. The results of the study show three main findings. First, the typology of post-disaster mosque functions is divided between limited empirical reality and strategic ideal potential, with mosques having spiritual, social, human, and physical assets that can be mobilized. Second, the revitalization of mosque functions is carried out through the utilization of spiritual-psychosocial assets for trauma recovery, social-network assets to strengthen social cohesion and build partnerships, and physical-economic assets for emergency markets, skills training, and optimization of productive waqf. Third, the asset-based da'wah strategy is formulated as an integrative model with da'wah bil-hal as the driving force, encompassing the stages of asset mapping, participatory planning, and sustainable implementation, as well as translating the values ​​of ta'awun, ukhuwwah, and maslahah into concrete actions. This study concludes that the asset-based da'wah strategy is able to transform mosques from passive entities into independent and sustainable recovery centers. Implementation of the research results can be done through policy integration, asset mapping by mosque administrators, preparedness training, multi-stakeholder partnerships, and mosque-based economic empowerment programs.